BIODETERIORATION AND BIODEGRADATION OF CULTURAL & RELIGIOUS HERITAGE MADE OF PAPER AS A WOOD DERIVATIVE - Rahmani, Tara Puri Ducha; Ismail, Ismail; Aziz, Isna Rasdianah (Universitas Islam Negeri Alauddin Makassar, 2022)
Many valuable cultural and religious heritage materials suffer from the process of biodeterioration and biodegradation, such as by the contamination of microbes—these contaminations affect the quality of the material as well as the health of the surrounding people. Several studies have been conducted to study the impacting entities as well as to overcome the biodeterioration and biodegradation problems. This review provides a fundamental definition of the said phenomenon and elaborates on the actions done by previous researchers with several approaches to identify and hinder future decay. This literature study compiles and selects previous studies to reach a conclusion. Fungi and bacteria are the two main classes of microorganisms responsible for biodegradation. Both of those organisms have the potential to degrade and deteriorate various types of cultural and religious heritage. The riskiest contamination for paper or manuscripts is brought on by fungi because of their capacity to degrade wood-based products. Additionally, the said microorganisms can have an impact on the health of those who are in close proximity to them, like librarians. The microbes have been studied, identified, and their growth has been prevented using various techniques. More research is still required to avoid the biodegradation and biodeterioration of the priceless cultural and religious heritage, as well as to develop techniques that are both effective and environmentally safe.